THE EFFECTIVENESS OF PEER ASSESSMENT IN DEVELOPING STUDENTS’ WRITING OF RECOUNT TEXT ( A pre-experimental study at second grade students in one of Public Senior High Schools in Garut, Indonesia) - R. Aulia Utami Hidayat (Institut Pendidikan Indonesia Garut, 2018)
This study is aimed at examining the effectiveness of peer assessment in developing students’ writing of recount text and to find out whether or not students give positive responses on the use of it. The participants of this study consisted of thirty-two learners from the second grade of a public senior high school in Garut. This study implemented pre-experimental design as the research method. The data were obtained from English writing ability test involving the pre-test and post-test in order to know the students’ writing ability before and after using peer assessment. The questionnaire as the second instrument of this research is given to the students to see their responses of the use of peer assessment. Both results of the instruments were analyzed quantitatively using SPSS Ver.24 and using the chart application on Microsoft Excel 2016. Therefore, the findings reveal that peer assessment is effective in developing students’ writing of recount text and students give the positive response on the use of it. Based on these findings, it is recommended to implement peer assessment in teaching and learning program.